GROSS HEPATIC CHANGES IN DEVELOPING ALBINO RATS EXPOSED TO VALPROIC ACID - Khan, Muhammad; Khattak, Sania Tanweer; Elahi, Maqbool (Journal of Ayub Medical College Abbottabad, 2011)
Background: Valproid Acid (VPA) is a broad spectrum antiepileptic drug. Its use during pregnancy has been associated with congenital anomalies and hepatotoxicity. This study was designed to assess the effects of VPA on the gross structure of liver in developing albino rats exposed to the drug during various trimesters of pregnancy. Methods: In this experimental study 40 pregnant rats were divided into 4 equal groups A, B, C and D. Group A received VPA in a dose of 500 mg/Kg/day intraperitonealy (I/P) on days 3, 4 and 5 of gestation. Group B received the drug in a dose of 500 mg/Kg/day I/P on days 8, 9 and 10 of gestation. Group C received VPA in a dose of 500 mg/Kg/day I/P on days 16, 17 and 18 of gestation. Group D received no treatment and was kept as a control group. On day 21, the rats were euthanised by cervical dislocation. The liver of the foetuses were dissected out for the assessment of their gross structure. Results: Foetal liver of the experimental groups showed significant decrease in weight as well as relative tissue weight index (RTWI) as compared to the control group, although the gross appearance of the foetal liver was normal in all the groups. Conclusion: The use of VPA during various trimesters of pregnancy produces hepatotoxicity in the developing rats. So, the use of this drug during pregnancy should be carefully decided. Keywords: Valproic acid, Developing albino rats, Hepatotoxicity